Impact of Women Dairy Self-Help Groups on Employment Generation of Women in Rajasthan - Rathore, Ritu; Malhotra, Ravinder; Mishra, Shubham (International Journal of Livestock Research, 2021)
The present study analysed the impact of women dairy self-help groups (SHGs) on employment generation in Rajasthan. The primary data was collected from 320 respondents and Heckman two stage econometric analysis was done for impact assessment. The findings show that the employment generation through dairy farming was significantly higher for SHG members than that of non-members. The variables education level, involvement in off-farm activities, annual income, and prior indebtedness had significant effect on women’s participation in dairy SHGs. Regression results show that the variable, participation dummy had significant impact on employment generation, which reveals that participation in SHG activities significantly increases the employment among women of the study area. Besides this, herd size, education level, formal training and land holding also had significant effect on employment generation of women. Hence, active participation of women in SHGs is suggested.